Festival Tourism as Part of International Tourism and a Factor in the Development of Cultural Tourism - Dychkovskyy, Stepan; Ivanov, Sergii (Information & Media, 2020)
The article examines that cultural tourism, by developing festival tours, is able to generate significant tourist flows not only by itself, but also it is a necessary complement to any other tourist product. The purpose. The aim is to analyze the scientific literature on intercultural research and the development of international tourist festivals. Results. The identification and discussion of the three main discourses of festival research made it possible to determine the role and impact of festivals in society and culture, the features of festival tourism and festival management. Classical discourse, emerging mainly from cultural anthropology and sociology, concerns the roles, meanings and influences of festivals in society and culture. Festivals are means for tourism, economic development and local marketing. At this discourse dominated. It is based on consumer behavior approaches and ignores the fundamental needs of celebration and many social and cultural reasons for searching a holiday. It should also be emphasized that festivals are increasingly being used to achieve social and cultural objects, which places them as implements for social marketers.